Enhancing the use of sustainable construction materials in southwest Nigeria: exploring the roles of quantity surveyors - Olatunde, Nathaniel Ayinde; Anugwo, Iruka Chijindu; Awodele, Imoleayo Abraham (Frontiers in Built Environment, 2025)
IntroductionThis study investigates the role of Quantity Surveyors (QS) in promoting the adoption of sustainable construction (SC) practices in Nigeria, to improve construction project performance in developing economies. Despite increasing awareness of the benefits of SC, its adoption remains low in Nigeria. Thus, this study advocates for a more active role of QS professionals in enhancing SC adoption and integration in construction activities.MethodsThe study employs a mixed-methods approach to data collection. In the first stage, a questionnaire was administered to 82 randomly selected professional registered Quantity Surveyors from Ekiti and Osun States, Nigeria, to gather quantitative data. In the second stage, structured interviews were conducted with 12 respondents from the initial survey, chosen for their high knowledge of SC, to gain in-depth insights and personal experience on the subject matter having obtained the participants’ written informed consent to participate in this study. Data were analyzed using descriptive statistics (frequency, percentage, mean item score) and inferential statistics (t-test), as well as content analysis for the qualitative data.ResultsThe findings reveal that while Quantity Surveyors possess significant knowledge of sustainable construction, their roles in facilitating the adoption of SC materials is low. The study identifies several key roles that QS professionals can play in enhancing SC adoption, including: driving stakeholder awareness, promoting life cycle costing, advising on alternative materials and their cost implications, contributing to policy formulation, advancing research and development initiatives, and conducting feasibility studies for sustainable development.DiscussionThe study is limited to data collected from Quantity Surveyors in two Southwestern Nigerian states, which may not fully represent the broader national context. The sampling method might introduce a level of limitation as regards the sample size and true representation of the target population. Future research could expand the sample size and geographic scope to gain a more comprehensive understanding of the role of QS in SC adoption across Nigeria and other developing countries. This research contributes to the literature on sustainable construction by highlighting the critical, yet under-explored, role of Quantity Surveyors in improving SC adoption in developing economies. The study emphasizes the potential for QS professionals to drive significant improvements in the sustainability of the construction sector, offering valuable insights for policymakers, practitioners, and the construction industry at large.